Development and validation of systems for genetic manipulation of the Old World tick-borne relapsing fever spirochete, Borrelia duttonii. - Clay D Jackson-Litteken; Wanfeng Guo; Brandon A Hogland; C Tyler Ratliff; LeAnn McFadden; Marissa S Fullerton; Daniel E Voth; Ryan O M Rego; Jon S Blevins (Public Library of Science (PLoS), 2024)
Relapsing fever (RF), a vector-borne disease caused by Borrelia spp., is characterized by recurring febrile episodes due to repeated bouts of bacteremia. RF spirochetes can be geographically and phylogenetically divided into two distinct groups; Old World RF Borrelia (found in Africa, Asia, and Europe) and New World RF Borrelia (found in the Americas). While RF is a rarely reported disease in the Americas, RF is prevalent in endemic parts of Africa. Despite phylogenetic differences between Old World and New World RF Borrelia and higher incidence of disease associated with Old World RF spirochete infection, genetic manipulation has only been described in New World RF bacteria. Herein, we report the generation of genetic tools for use in the Old World RF spirochete, Borrelia duttonii. We describe methods for transformation and establish shuttle vector- and integration-based approaches for genetic complementation, creating green fluorescent protein (gfp)-expressing B. duttonii strains as a proof of principle. Allelic exchange mutagenesis was also used to inactivate a homolog of the Borrelia burgdorferi p66 gene, which encodes an important virulence factor, in B. duttonii and demonstrate that this mutant was attenuated in a murine model of RF. Finally, the B. duttonii p66 mutant was complemented using shuttle vector- and cis integration-based approaches. As expected, complemented p66 mutant strains were fully infectious, confirming that P66 is required for optimal mammalian infection. The genetic tools and techniques reported herein represent an important advancement in the study of RF Borrelia that allows for future characterization of virulence determinants and colonization factors important for the enzootic cycle of Old World RF spirochetes.